2006
DOI: 10.1007/s10820-006-9010-4
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Silicon Suboxides: Chemical and Mechanical Forces on the Atomic Scale

Abstract: Silicon suboxides play an important role in different industrial applications, particularly in the form of the Si-SiO 2 interface, which is one of the key elements in present day microelectronics and potentially in future nano-electronics as well. This paper focuses on the chemical and mechanical effects related to the existence of different oxidation states of Si atoms in SiO x systems with various Si:O composition and topology, such as O atoms in Si, the Si-SiO 2 interface, and O vacancies in SiO 2 . We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Interfacial Stresses during Oxidation. The interfacial stress, which can be thought as a combination of chemical and mechanical (physical) stresses, 65 plays an important role in the reliability of gate oxides with its ultrathin interface. 63 The chemical stress at the interface is associated with Si atoms that have an intermediate oxidation state between 0 (in Si) and 4+ (in SiO 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interfacial Stresses during Oxidation. The interfacial stress, which can be thought as a combination of chemical and mechanical (physical) stresses, 65 plays an important role in the reliability of gate oxides with its ultrathin interface. 63 The chemical stress at the interface is associated with Si atoms that have an intermediate oxidation state between 0 (in Si) and 4+ (in SiO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stress causes the deformation of bonds and bond angles at the interface. Korkin et al 65 suggested that the chemical and the mechanical stress make comparable contributions to the total Si|SiO 2 interface stress.…”
Section: Resultsmentioning
confidence: 99%